Anticipatory capacity in response to global change across an extreme elevation gradient in the Ica Basin, Peru - de Grenade, R.; Rudow, J.; Taboada Hermoza, R.; Adauto Aguirre, M.E.; Scott, C.A.; Willems, B.; De La Rosa, J.L.; Varady, R.G. (Springer Verlag, 2017)
Mountainous areas with extreme elevation gradients and corresponding ranges of biophysical and socioeconomic conditions are highly vulnerable to global change. We propose that the ability to anticipate changes in weather, markets, and the availability and cost of resources is crucial to livelihoods and a key component of adaptive capacity. We conducted research in the Ica Basin, an Andes–Pacific watershed in Peru, to assess farmers’ capacity to anticipate changing hydroclimatic and production scenarios as a prerequisite to alter their activities in a way that positively affects livelihoods. We employed a mixed-methods approach to understand how local impacts of global change across the gradient differentially undermine farmers’ resilience and open opportunities for anticipatory and adaptive responses. We find that most farmers have little access to modern weather forecasts or market conditions, even though weather stations are located throughout the basin and many farmers have cellphone, television, and Internet services. Meteorological and hydrologic stations often are not maintained because of difficult physical access, and extreme gradients affect the reach, reliability, and cost of telecommunication networks. Unsurprisingly, farmers who do have reliable advance information on climate, market, and extension service availability are those in the coastal lowland agro-export sector. Smallholders in the lowlands and producers upstream in the basin fare far worse in this respect. Social, political, and environmental conditions have shifted rapidly, eroding traditional knowledge and information networks, and informal social networks cannot keep pace with changing scenarios. Increasing information access and improving telecommunication services in rural areas would strengthen farmers’ proactive decision-making capacity and lead to greater adaptive capacity and more uniform social-ecological resilience over the gradient in the basin.
Keywords: Anticipatory capacity; Adaptive capacity; Ica Basin; Global change; Peru; https://purl.org/pe-repo/ocde/ford#1.05.10